2023
DOI: 10.3390/en16052142
|View full text |Cite
|
Sign up to set email alerts
|

Applied Complex Diagnostics and Monitoring of Special Power Transformers

Abstract: As a major component in electric power systems, power transformers are one of the most expensive and important pieces of electrical equipment. The trouble-free operation of power transformers is an important criterion for safety and stability in a power system. Technical diagnostics of electrical equipment are a mandatory part of preventing accidents and ensuring the continuity of the power supply. In this study, a complex diagnostic methodology was proposed and applied for special power transformers’ risk est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…It is calculated by taking the sum of absolute differences between predicted and actual values and dividing it by the number of observations. The formula for the MAE is given in Equation (2).…”
Section: Evaluation Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is calculated by taking the sum of absolute differences between predicted and actual values and dividing it by the number of observations. The formula for the MAE is given in Equation (2).…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…To ensure the stability and reliability of the power system, it is crucial to monitor, maintain, diagnose, and upgrade transformers regularly. This helps prevent costly accidents and damage, extend transformer life, increase grid reliability, and reduce maintenance costs [2][3][4]. Accurately evaluating the condition of power transformers is essential for creating and sustaining a highly reliable power system [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the relevance of developing techniques for defining the transformer resource in the smart energy paradigm [18,19]. Ref.…”
Section: The Relevance Of Improving the Rul Forecasting Techniquesmentioning
confidence: 99%
“…Currently, two basic approaches are used to estimate and forecast the equipment state-based on the health index (HI) and the RUL. It is believed that HI is a standard tool for the comprehensive assessment of insulation aging [33,34] and load [35] and the analysis of the performance, risk, and reliability of transformers [19,36,37]. Ref.…”
Section: The Relevance Of Improving the Rul Forecasting Techniquesmentioning
confidence: 99%
See 1 more Smart Citation